Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To find the possible values for [tex]\( c \)[/tex], we need to compare coefficients from the given polynomial equation [tex]\((a x + 9)(b x + 2) = 27 x^2 + c x + 18\)[/tex].
Let's start by expanding the left-hand side of the given equation:
[tex]\[ (a x + 9)(b x + 2) = a b x^2 + 2 a x + 9 b x + 18 \][/tex]
Combining like terms, the polynomial becomes:
[tex]\[ a b x^2 + (2 a + 9 b) x + 18 \][/tex]
We can now compare coefficients from both sides of the equation:
[tex]\[ a b x^2 + (2 a + 9 b) x + 18 = 27 x^2 + c x + 18 \][/tex]
From comparing the coefficients, we obtain the following equations:
1. [tex]\(a b = 27\)[/tex]
2. [tex]\(2 a + 9 b = c\)[/tex]
3. The constant term 18 is the same on both sides, so no new information is required from it.
Additionally, we are given another condition:
[tex]\[ a + b = 12 \][/tex]
We now have a system of equations to solve:
[tex]\[ \begin{cases} a b = 27 \\ a + b = 12 \end{cases} \][/tex]
We can solve this system step-by-step:
1. From [tex]\(a + b = 12\)[/tex], express [tex]\( b \)[/tex] in terms of [tex]\( a \)[/tex]:
[tex]\[ b = 12 - a \][/tex]
2. Substitute [tex]\( b = 12 - a \)[/tex] into [tex]\( a b = 27 \)[/tex]:
[tex]\[ a (12 - a) = 27 \][/tex]
This simplifies to:
[tex]\[ 12a - a^2 = 27 \][/tex]
[tex]\[ a^2 - 12a + 27 = 0 \][/tex]
3. Solve this quadratic equation for [tex]\( a \)[/tex] using the quadratic formula [tex]\( a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex]:
[tex]\[ a = \frac{12 \pm \sqrt{144 - 108}}{2} \][/tex]
[tex]\[ a = \frac{12 \pm \sqrt{36}}{2} \][/tex]
[tex]\[ a = \frac{12 \pm 6}{2} \][/tex]
This gives us two possible values for [tex]\( a \)[/tex]:
[tex]\[ a = \frac{18}{2} = 9 \quad \text{or} \quad a = \frac{6}{2} = 3 \][/tex]
4. Calculate the corresponding values for [tex]\( b \)[/tex]:
[tex]\[ \text{If } a = 9, \text{ then } b = 12 - 9 = 3 \][/tex]
[tex]\[ \text{If } a = 3, \text{ then } b = 12 - 3 = 9 \][/tex]
5. Finally, substitute [tex]\( a \)[/tex] and [tex]\( b \)[/tex] into [tex]\( 2a + 9b = c \)[/tex] to find the possible values of [tex]\( c \)[/tex]:
[tex]\[ \text{If } a = 9 \text{ and } b = 3, \text{ then } \][/tex]
[tex]\[ c = 2(9) + 9(3) = 18 + 27 = 45 \][/tex]
[tex]\[ \text{If } a = 3 \text{ and } b = 9, \text{ then } \][/tex]
[tex]\[ c = 2(3) + 9(9) = 6 + 81 = 87 \][/tex]
Thus, the two possible values for [tex]\( c \)[/tex] are 45 and 87, which corresponds to option (C).
The correct answer is:
[tex]\[ \boxed{45, 87} \][/tex]
Let's start by expanding the left-hand side of the given equation:
[tex]\[ (a x + 9)(b x + 2) = a b x^2 + 2 a x + 9 b x + 18 \][/tex]
Combining like terms, the polynomial becomes:
[tex]\[ a b x^2 + (2 a + 9 b) x + 18 \][/tex]
We can now compare coefficients from both sides of the equation:
[tex]\[ a b x^2 + (2 a + 9 b) x + 18 = 27 x^2 + c x + 18 \][/tex]
From comparing the coefficients, we obtain the following equations:
1. [tex]\(a b = 27\)[/tex]
2. [tex]\(2 a + 9 b = c\)[/tex]
3. The constant term 18 is the same on both sides, so no new information is required from it.
Additionally, we are given another condition:
[tex]\[ a + b = 12 \][/tex]
We now have a system of equations to solve:
[tex]\[ \begin{cases} a b = 27 \\ a + b = 12 \end{cases} \][/tex]
We can solve this system step-by-step:
1. From [tex]\(a + b = 12\)[/tex], express [tex]\( b \)[/tex] in terms of [tex]\( a \)[/tex]:
[tex]\[ b = 12 - a \][/tex]
2. Substitute [tex]\( b = 12 - a \)[/tex] into [tex]\( a b = 27 \)[/tex]:
[tex]\[ a (12 - a) = 27 \][/tex]
This simplifies to:
[tex]\[ 12a - a^2 = 27 \][/tex]
[tex]\[ a^2 - 12a + 27 = 0 \][/tex]
3. Solve this quadratic equation for [tex]\( a \)[/tex] using the quadratic formula [tex]\( a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex]:
[tex]\[ a = \frac{12 \pm \sqrt{144 - 108}}{2} \][/tex]
[tex]\[ a = \frac{12 \pm \sqrt{36}}{2} \][/tex]
[tex]\[ a = \frac{12 \pm 6}{2} \][/tex]
This gives us two possible values for [tex]\( a \)[/tex]:
[tex]\[ a = \frac{18}{2} = 9 \quad \text{or} \quad a = \frac{6}{2} = 3 \][/tex]
4. Calculate the corresponding values for [tex]\( b \)[/tex]:
[tex]\[ \text{If } a = 9, \text{ then } b = 12 - 9 = 3 \][/tex]
[tex]\[ \text{If } a = 3, \text{ then } b = 12 - 3 = 9 \][/tex]
5. Finally, substitute [tex]\( a \)[/tex] and [tex]\( b \)[/tex] into [tex]\( 2a + 9b = c \)[/tex] to find the possible values of [tex]\( c \)[/tex]:
[tex]\[ \text{If } a = 9 \text{ and } b = 3, \text{ then } \][/tex]
[tex]\[ c = 2(9) + 9(3) = 18 + 27 = 45 \][/tex]
[tex]\[ \text{If } a = 3 \text{ and } b = 9, \text{ then } \][/tex]
[tex]\[ c = 2(3) + 9(9) = 6 + 81 = 87 \][/tex]
Thus, the two possible values for [tex]\( c \)[/tex] are 45 and 87, which corresponds to option (C).
The correct answer is:
[tex]\[ \boxed{45, 87} \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.